JUSTIFICATION OF THE RIGHT TO BUILD ON AGRICULTURAL LAND - Zhivkovska, Rodna; Lalevska, Tea (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Agricultural land, as defined by comparative law, the Macedonian Ownership and Other Real Rights Act, and the subject-specific laws on agricultural land, is considered a thing of public interest and should be used for agricultural purposes. The Agricultural Land Act promotes its rational use, with the primary aim of producing agricultural products. Regarding this aim, the Law allowed the construction of facilities on that land, which should enable the cultivation of agricultural products and benefit from it. Also, the Macedonian legal system has expanded the list of types of facilities that may be built on that land. In practice, this expansion has led to extensive construction on that land. As a result, nowadays, the agricultural land is used more for tourism and sports, rather than increasing the yield of agricultural production. In addition, these legal norms have contributed to the increase in the import of agricultural products from abroad, creating disadvantages for domestic production. Therefore, in this paper, we will address the issue of how the Macedonian legal system can resolve this social conflict through new legal norms.Keywords: law, agricultural land, construction, public interest.
Keywords: law; agricultural land; construction; public interest